PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI AKUNTANSI PADA KING’S GOOD - Tintus Wijaya; Leo Willyanto Santoso; Silvia Rostianingsih (Jurnal Infra, 2013)
King’s Good is business unit engaged in the sale of material japan foodstuff are located in the city of East Java, Sidoarjo. In daily activities King’s Good is still applying the manual system and not at all contained there in accounting processes. This causes the transaction process is slow and less accurate when compared to using a computerized system. Therefore King’s Good requires a computerized accounting information systems, hoping to overcome the problems encountered. Accounting information system is expected to help shop owners in the records of all transactions carried out and process them into useful reports for the owner for future store development.The design of the system design using Data Flow Diagram and Entity Relationship Diagram. Program using Microsoft SQL Server 2005 as database, and using Microsoft Visual Studio 2005 .NET as programming language. The scope of the program that created the master database to include master supplier, customer, item, price, and units. The transaction includes the purchase and sale transactions, as well as journaling is automatically.From the results of the questionnaire, overall applications have been made in accordance with company requirements. Produced accurate reports in accordance with the manual calculation. In addition the program design and ease of use between the menu is well regarded by most users.